SHAPING TECHNIQUES TO INCREASE INDEPENDENCE IN TAKING A BATH FOR MIDDLE AGED ADULTS WITH MODERATE INTELECTUAL DISABILITY AT WISMA DEMPO - Biyanti, Yosephin Aris; Wulandari, Nawang Warsi; Widodo, Rinto Wahyu (LPPM Universitas 17 Agustus 1945 Samarinda, 2024)
Abstract The problem that often occurs in people with intelectual disability is the ability to be independent, namely taking care of themselves such as bathing, dressing and toileting . The ability to take care of oneself is a basic skill that everyone must have, so independence is important. Independence is being able to independently and not depend on the help or support of other people which is characterized by being able to meet physical and psychological needs. The more someone can be independent, the higher their self-confidence and happiness, while the more they depend on others, the more they feel inadequate and disappointed. This research was conducted at Dempo Malang homestead. The research subjects were two moderately intelectually disabled people who were not yet independent in terms of bathing, female and middle-aged adults. The purpose of this study was to find out whether shaping techniques can increase the independence of people with moderate intelectual disability at Wisma Dempo, Malang The research uses an experiment method. Research design is A-B-A with Single Subject Research approach. Data collection uses participant observation. The results show that the shaping technique can increase the bathing independence of two people with moderate intelectual disability. Keywords: Shaping Technique, Independency in taking a bath, Moderate Intelectual Disability